THE SEEDLING GROWTH RESPONSE OF PISUM SATIVUM L. TO DIFFERENT TYPES OF COMPOST - Bina JAMSHER; Muhammad ZAFAR IQBAL; Muhammad SHAFIQ; Mohammad ATHAR (Journal of Applied Life Sciences and Environment)
The constant increase in the high number of population, anthropogenic and industrial activities are alarming issues and raise food security issues around the world. The treatment of compost acts as an effective and environmentally friendly tool for an increase in vegetable production. This research article records the effects of three soil compost treatments (1) dry leaves (Ficus bengalensis L.), (2) solid waste (mustard oil cake) and (3) chicken manure, alone and in combination, with seedling growth performances of pea in pot culture experiments with five replications. The results showed that soil compost treatments showed a significant (p < 0.05) impact on the physicochemical features of soil and the physiological characteristics of pea (Pisum sativum L.). Soil compost analysis revealed a difference in soil porosity and pH, electrical conductivity, organic matter, total organic carbon, CaCO3, Na+, K+, phosphorous and nitrogen. Plant tissue analysis of pea seedlings also showed different levels of sodium, potassium and phosphorous values. The findings of the present research work concludes that the treatment of F. bengalensis dry leaves (25%) + garden loam (75%) treatment produced maximum growth performance, and the mustard oil cake solid waste (25%) + garden loam (75%) treatment showed the lowest seedling growth performance. The F. bengalensis dry leaves (25%) + garden loam (75%), soil compost application treatment showed the maximum seedling height of pea. The solid waste (SW) mixed with garden loam (GL) (SW 25% + GL 75%) and mustard oil cake solid waste alone treatment showed the lowest seedling growth of pea. The F. bengalensis dry leaves 25% + garden loam 75% compost treatment also influenced on the soil properties.